Power quality concerns in assessing the impacts of nonlinear loads in Fakulti Teknologi Maklumat Sains dan Komputer (FTMSK) building / Kamarul Hisyam Kamaruzzaman - Kamaruzzaman, Kamarul Hisyam (2001)
This project mainly explained of how well predictive maintenance can be used to prevent and avoid power problems in electrical systems due to non-linear loads. It also gives a general outline of the analysis methods for harmonics and presents results obtained from field measurement. It also focused on the effects of high content of harmonic, overload and loose connection in the distribution systems that cause power quality problems. This project report summarizes some of the results of survey and monitoring of quality of electricity supply conducted at Faculty of Computer Science (FTMSK), MARA University of Technology (UiTM) using Reliable Power Meter (RPM) and supported by thermograms captured using infrared thermography (IR) camera. . The aim of the project is to understand the available theory and correlation with the actual cases referring to Residual Current Circuit Breakers (RCCB's) nuisance tripping at FTMSK as a case study. The survey and monitoring were performed at incoming point supply of the Main Switch Board (MSB) down to the loads at final distribution board of FTMSK. Data analysis of voltage and current events was monitored using RPM whereas IR camera is used for capturing unequal temperature at all current carrying conductor of the supply distribution to assist analysis and problem's diagnosis. A special interest goes to the assessment of the harmonics; type of perturbations induced by the load users of FTMSK and supported evidence from thermograms related to assessment of harmonics. Thermograms also used in detecting neutral overload and bad termination. High harmonic content, neutral overload and bad termination causes problem and failure to the operation of the equipment, due to protection device tripping and for future concerns are discussed together with the recommended solutions. Mitigation of harmonics until meets the IEEE standards also discussed in brief.